2019
DOI: 10.1080/08897077.2018.1488335
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects of Interoceptive Awareness Training through Mindful Awareness in Body-Oriented Therapy (MABT) for Women in Substance use Disorder Treatment

Abstract: Findings that interoceptive training is associated with health outcomes for women in SUD treatment are consistent with emerging neurocognitive models that link interoception to emotion regulation and to related health outcomes, providing knowledge critical to supporting and improving SUD treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 79 publications
3
61
1
Order By: Relevance
“…The gentle, coached MABT approach is thus used to facilitate learning, and also helps to build trust and comfort with the material, slowly increasing sensitivity to internal states and awareness of complex internal responses that can shape awareness, self-understanding, decision making processes, and behavior that underlie regulation. MABT research in community settings demonstrates the feasibility, acceptability, and safety of MABT ( Price, 2005 , 2006 ; Price et al, 2007 , 2012 , 2013 ; Price and Crowell, 2016 ). These studies involved samples with co-occurring conditions and extensive trauma histories, highlighting the acceptability of MABT teaching processes among highly distressed populations.…”
Section: Section Ii: Mindful Awareness In Body-oriented Therapymentioning
confidence: 99%
“…The gentle, coached MABT approach is thus used to facilitate learning, and also helps to build trust and comfort with the material, slowly increasing sensitivity to internal states and awareness of complex internal responses that can shape awareness, self-understanding, decision making processes, and behavior that underlie regulation. MABT research in community settings demonstrates the feasibility, acceptability, and safety of MABT ( Price, 2005 , 2006 ; Price et al, 2007 , 2012 , 2013 ; Price and Crowell, 2016 ). These studies involved samples with co-occurring conditions and extensive trauma histories, highlighting the acceptability of MABT teaching processes among highly distressed populations.…”
Section: Section Ii: Mindful Awareness In Body-oriented Therapymentioning
confidence: 99%
“…Somewhat simpler studies, without that type of mediation analysis, have shown that changes in interoceptive awareness were found in parallel with changes in clinical outcomes. Examples include integrative, body-awareness-focused movement exercises for posttraumatic stress disorder (PTSD; Mehling, Chesney, et al, 2018); mindful awareness in body-oriented therapy for substance-use disorder (Price et al, 2019a(Price et al, , 2019b; Qigong for postsurgical pain in patients with breast cancer (Osypiuk et al, 2020); and other mindfulness-based interventions for women with obesity (Daubenmier et al, 2016) or for hypertension (Loucks et al, 2019). The analyses in the latter studies support the hypotheses that the improvements in clinical outcomes may potentially be associated with improvements in interoceptive bodily awareness, but without mediation analysis, these studies are unable to confirm that this improvement in a clinical outcome occurred because of improved bodily awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Mindful Awareness in Body-Oriented Therapy (MABT) is a manualized, mindfulness-based approach that is designed to teach interoceptive skills for self-care [23]. Interoception is the ability to process signals that originate in the body and is broadly described as the overall sensations, or state, of the body [60].…”
Section: Mindful Awareness In Body-oriented Therapy (Mabt) Overview Omentioning
confidence: 99%
“…Stage 2 of the MABT program (sessions 3 and 4) is directed at learning and developing strategies for interoceptive awareness (access), which is a more advanced aspect of body literacy that adds upon the skills learned in the first stage [23]. This stage focuses on sensations that are still quite overt and apparent, such as the sensation of breathing in and out, but clients are beginning to refine their bodily awareness.…”
Section: Mindful Awareness In Body-oriented Therapy (Mabt) Overview Omentioning
confidence: 99%
See 1 more Smart Citation